Borzeguim by Antônio Carlos Jobim: The Power of a Popular Song to Awaken Environmental Awareness (Global Journal of Human-Social Science, 2025)
Based on José Miguel Wisnik's proposition that popular song is a way of thinking about the world, and therefore a kind of "Gay Science", to use the term originally coined by Nietzsche, this paper aims to analyse the song "Borzeguim" by Antonio Carlos Jobim in order to understand its potential for developing ecological sensitivity. As theoretical framework, I will use the proposals of José Miguel Wisnik and Luiz Tatit, as well as the contributions of critics of Jobim's work, such as the academic André Rocha L. Haudenschild. The main thesis I'm trying to defend is that Jobim's songs have points of contact with concrete poetry, with indigenous Brazilian rhythms (inspired by the work of the master Villa-Lobos) and with elements of popular culture (indigenous mythology and sertaneja prophecy). Borzeguim is the Jobinian way of thinking about the world through the lens of the imagination. It's a warning and a lament for these times of environmental crisis.
Keywords: popular song; gay science; borzeguim; atlantic forest; environmental awareness